(untitled) (Al-Academy, 2023)
The use of symbols is considered an important part of visual expression since ancient civilizations till the present time, and detecting the significance of these symbols is a communication means between the artwork and the recipient. The current study aims to detect the clarification of the concept of symbolic connotations, and to detect their importance in the works of the artist Eugene Delacroix, through description and technical analysis, and trying to monitor the technical aspects of these connotations and using them in forming the artwork; This shows the importance of the study in trying to benefit the scholars in the field of visual arts and the analysis of artworks in particular. The study used the descriptive analytical approach for detecting and analyzing these connotations to reach results related to the research objectives. The research sample consisted of paintings of the artist’s works during the period (1822-1837 AD), where the works were sorted according to the specified time period, taking into account the stages and transformations in the artistic style. The artworks were chosen as a purposive sample; The number of artworks reached (4), they represent two important stages for the artist: the European stage, and the Arab Maghreb stage. The study reached several results, the most prominent of which are: the association of formative formulations in Delacroix’s works according to the two artistic stages that he lived in Europe and Morocco. Also, the artist used in some of his works various symbolic connotations; the most important of which are: the conventional, explanatory and aesthetic connotations, which are among the direct symbolic connotations; The artist also used indirect symbolic connotations such as suggestive and probable connotations, and all these connotations have implicit meanings. Following the results of the study, the current study reached a set of recommendations, the most important of which are supporting the studies and researches associated to analyzing symbolic connotations in the local artworks